HOUT-29. COMORBIDITIES IN SURVIVAL OF ADULTS WITH A GLIOBLASTOMA - Firkins, Jenny (Neuro Oncol, 2017)
INTRODUCTION: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor. A wide range of patient comorbid conditions such as obesity, hypertension, hyperlipidemia and type II diabetes mellitus (DM) may impact treatment-related complications and outcomes. METHODS: This retrospective, IRB-approved study included 140 adults with pathology-confirmed GBM (WHO grade IV) who initiated chemo-radiation as first line treatment from 2002 to 2016 at Oregon Health & Science University. A total of 140 subjects were included for analysis, 75 of these subjects were simultaneously enrolled in 1 of 3 prospective IRB-approved magnetic resonance imaging studies using ferumoxytol iron oxide nanoparticles as contrast agent. No grade 3 or 4 toxicities were seen with the administration of ferumoxytol, this is consistent with the results of a larger review of 671 administrations of ferumoxytol (Varallyay et al, AJNR in press). Body Mass Index (BMI) was calculated based on primary chemotherapy dose. Comorbidities were defined by American Heart association guidelines. Survival was correlated with comorbidities and adjusted with known predictors of survival: age at diagnosis, performance status at diagnosis, extent of tumor resection, and MGMT methylation status. No difference in survival was seen between subjects who received ferumoxytol and those who did not. RESULTS: Being overweight was associated with a 28% decrease in survival (p=0.039) and hypertension was associated with a 57% increase in survival (p=0.041). CONCLUSION: We conclude that a higher BMI at diagnosis may adversely impact survival in patients with glioblastoma. Future studies are needed to determine if BMI should be considered a variable for risk stratification and survival analysis for patients with GBM. In our cohort, hypertension was associated with an increase in survival; this could be due to initiation of aggressive monitoring and medical interventions to manage hypertension, though the exact mechanism for both of these results is yet to be determined.